2021
DOI: 10.1097/iop.0000000000002093
|View full text |Cite
|
Sign up to set email alerts
|

Upper Eyelid Contour Changes After Orbital Decompression in Graves Orbitopathy

Abstract: Purpose: To evaluate the effect of orbital decompression on the upper eyelid contour. Methods: A paired cross-sectional analysis of the upper eyelid contour was performed for 103 eyes of 66 patients who underwent orbital decompression. A control group of 26 normal subjects was also included. The eyelid contour of all participants were measured with Bézier lines adjusted to the eyelid contour and 9 midpupil eyelid margin (MPD) distances from a horizontal line bisecting the pupil. One central, corresponding to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…Moreover, studies have demonstrated that there may be a decrease or increase in the amount of white adipose tissue as a result of metabolic changes, while brown adipose tissue is generally stable and provides thermodynamic balance [29]. On the other hand, the fact that ROF can be surgically removed during the treatment of exophthalmos developing, particularly in diseases such as Graves' disease, has increased the scientific interest in ROF tissue [30]. However, there is no study in the literature investigating the effect of LHRH agonists on ROF.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies have demonstrated that there may be a decrease or increase in the amount of white adipose tissue as a result of metabolic changes, while brown adipose tissue is generally stable and provides thermodynamic balance [29]. On the other hand, the fact that ROF can be surgically removed during the treatment of exophthalmos developing, particularly in diseases such as Graves' disease, has increased the scientific interest in ROF tissue [30]. However, there is no study in the literature investigating the effect of LHRH agonists on ROF.…”
Section: Discussionmentioning
confidence: 99%
“…14 The second step, as required, is strabismus surgery. The final third step, if indicated, is eyelid repositioning surgery, since eyelid position can be affected by both bony decompression [14][15][16][17] and strabismus surgery. 18,19 This staged approach is still generally utilized, although some authors have reported successful outcomes in combining these surgical stages to decrease trips to the operating room and compress the time for surgical rehabilitation.…”
Section: Stagingmentioning
confidence: 99%
“… 1 , 2 , 3 Furthermore, the assessment of eyelid contour using midpupil lid distance (MPLD) was often focused on the upper eyelid of adults. 4 , 5 , 6 There is a lack of comprehensive eyelid contour measurements which contain both upper and lower eyelids in different genders of all ages.…”
mentioning
confidence: 99%